Pilot whole-exome sequencing of a German early-onset Alzheimer's disease cohort reveals a substantial frequency of PSEN2 variants - Blauwendraat, Cornelis; Wilke, Carlo; Jansen, Iris E.; Schulte, Claudia; Simón-Sánchez, Javier; Metzger, Florian G.; Bender, Benjamin; Gasser, Thomas; Maetzler, Walter; Rizzu, Patrizia; Heutink, Peter; Synofzik, Matthis (Neurobiology of aging, 2016)
Early-onset Alzheimer's disease (EOAD) accounts for 1%–2% of all Alzheimer's disease (AD) subjects, with large variation in the reported genetic contribution of known dementia genes. In this pilot study, we genetically characterized a German EOAD cohort (23 subjects) by whole-exome sequencing, capturing variants in all recognized AD and frontotemporal dementia genes. After variant filtering, we identified 7 events of altogether 6 different rare variants in 6 subjects, including 4 novel variants. Four of the 6 variants, observed in 5 different index subjects (5/23 = 22%), were considered to be possibly pathogenic. These included 2 presenilin 2 (PSEN2) variants (p.N141I—previously denoted as a Volga German variant, observed in 2 index subjects; and p.L238P), 1 amyloid precursor protein (p.I716M), and 1 presenilin 1 (ΔE9). Using a control exome data set of 96 ethnically matched neurodegenerative disease controls (Parkinson's disease), we identified only 1 variant (PSEN2 p.T18M) (1%), demonstrating a significantly higher mutational burden in the EOAD group (p > 0.0001). Our findings demonstrate a substantial frequency of variants in dementia genes in EOAD, including several seemingly “sporadic” subjects. This indicates that heritability in EOAD might be higher than assumed. The finding of 3 subjects carrying potential pathogenic PSEN2 variants suggests that, in specific populations PSEN2 variants might be as frequent as (or more frequent than) presenilin 1, for example, in German populations which are influenced by Volga German heritage. Variants in AD genes were also associated with rare phenotypes such as frontal AD or primary progressive aphasia, demonstrating the need to screen AD genes in frontotemporal dementia-like phenotypes.